Relatedness with plant species in native community influences ecological consequences of range expansions. Issue 7 (6th February 2018) - Koorem, Kadri; Kostenko, Olga; Snoek, L. Basten; Weser, Carolin; Ramirez, Kelly S.; Wilschut, Rutger A.; van der Putten, Wim H.
Abstract : Global warming is enabling many plant species to expand their range to higher latitudes and altitudes, where they may suffer less from natural aboveground and belowground enemies. Reduced control by natural enemies can enable climate warming‐induced range expanders to gain an advantage in competition with natives and become disproportionally abundant in their new range. However, so far studies have only examined individual growth of range expanders, which have common congeneric plant species in their new range. Thus it is not known how general is this reduced effect of above‐ and belowground enemies and how it operates in communities, where multiple plant species also interact with each other. Here we show that range‐expanding plant species with and without congenerics in the invaded habitats differ in their ecological interactions in the new range. In a community‐level experiment, range‐expanding plant species, both with and without congenerics, suppressed the growth of a herbivore. However, only range expanders without congenerics reduced biomass production of the native plant species. In the present study, range expanders without congenerics allocated more biomass aboveground compared to native plant species, which can explain their competitive advantage. Competitive interaction and also biomass allocation of native plants and their congeneric range expanders were similar. Our results highlight that information about species phylogenetic relatedness with native flora can be crucial for improving predictions about the consequences of climate warming‐induced range expansions.